Entitlement, Epistemic Risk, and Scepticism. (28th December 2021) - Moretti, Luca
Abstract: Crispin Wright maintains that the architecture of perceptual justification is such that we can acquire justification for our perceptual beliefs only if we have antecedent justification for ruling out any sceptical alternative. Wright contends that this principle doesn't elicit scepticism, for we are non-evidentially entitled to accept the negation of any sceptical alternative. Sebastiano Moruzzi has challenged Wright's contention by arguing that since our non-evidential entitlements don't remove the epistemic risk of our perceptual beliefs, they don't actually enable us to acquire justification for these beliefs. In this paper I show that Wright's responses to Moruzzi are ineffective and that Moruzzi's argument is validated by probabilistic reasoning. I also suggest that Wright couldn't answer Moruzzi's challenge without weakening the support available for his conception of the architecture of perceptual justification.